Minimization of electrical losses in industrial systems using genetic algorithm - Ñauapari Huatuco, Zocimo (2018)
This paper proposes a procedure to minimize electrical losses present in industrial systems, through a specific program developed for this purpose, based on Genetic Algorithm, and written using MATLAB instructions.The minimization is realized with the placement of shunt capacitors connected to the buses. For validation of the proposed method, it is considered accuracy and speed, and the developed program´s results are compared with the results produced by traditional programs. The program avoids leading power factor at the bus connected with the power distribution company and the user may determine buses where he does not want the installation of capacitors. The Genetic Algorithm's fitness, responsible for guiding the optimization process, is the active power loss. Finally,  the program is applied to minimize active losses present at an industrial system, 38 buses.